1.Uzupełnij:
6 - ... = 9
-4 - ... =1
-7 - ... =-10
0 - ... =7
... - (-6) = -9
... - (-4) = 0

2. Oblicz.
6 * (-9)=
(-10) * 1,5=
(-4) * 1/2=
(-2/3) * (-2/5)=
(-18) : 3=
2,2 : (-2)=
0,8 * (-5)=
(-9) * (-2/3)=
(-3) : (-1/3)=
(-1/2)do potęgi 3
(-0,06) do potęgi 2
(-1/3) do potęgi 4
(-0,5) do potęgi 3

3

Odpowiedzi

Najlepsza Odpowiedź!
2010-03-22T18:08:58+01:00
1.Uzupełnij:
6 - .(-3).. = 9
-4 - ..(-5). =1
-7 - .3.. =-10
0 - .(-7).. =7
.-15.. - (-6) = -9
..-4. - (-4) = 0

2. Oblicz.
6 * (-9)= -45
(-10) * 1,5= -15
(-4) * 1/2= -2
(-2/3) * (-2/5)= 4/15
(-18) : 3= -6
2,2 : (-2)= -1,1
0,8 * (-5)= -4
(-9) * (-2/3)= 6
(-3) : (-1/3)= 9
(-1/2)do potęgi 3 = -1/8
(-0,06) do potęgi 2 = 0,0036
(-1/3) do potęgi 4 = 1/81
(-0,5) do potęgi 3 = - 0,125
2 5 2
2010-03-22T18:11:38+01:00
6 - (-3)= 9
-4 - (-5) = 1
-7 - 3 = -10
0 - (-7) = 7
-15 - (-6) = -9
-4 - (-4) = 0




2.
6 * (-9)= -54
(-10) * 1,5= - 15
(-4) * 1/2= -2
(-2/3) * (-2/5)= 4/15
(-18) : 3= -6
2,2 : (-2)= -1,1
0,8 * (-5)= - 4
(-9) * (-2/3)= 6
(-3) : (-1/3)= 9
(-1/2)do potęgi 3 = 0,125
(-0,06) do potęgi 2 = 0,0036
(-1/3) do potęgi 4 = 1/81
(-0,5) do potęgi 3 = =0,125
2010-03-22T18:14:49+01:00
1
*-3
*-5
*3
*-7
*-15
*-4

2.
*-54
*-15
*-2
*4/15
*-6
*-1,1
*-4
*6
*9
*-1/8
*0,0036
*1/81
*-0.125